DAMPAK PEMBANGUNAN BREAKWATER TERHADAP STRUKTUR KOMUNITAS POLYCHAETA DI PESISIR PANTAI MANOKWARI, PAPUA BARAT - Diana Elsa Albita Wambrauw; Keliopas Krey; Sita Ratnawati (VOGELKOP: Jurnal Biologi, 2018)
ABSTRACTBreakwater is a small structures designed to protect coastal area from extremely sea waves exposure. The breakwater has been used in many coastal area at various town in Papua include Manokwari Regency, West Papua Province. Breakwaters designed at Manokwari has been reduce the intensity of wave action in inshore waters. Moreover, the breakwater also reduce coastal erosion and provide safe harbourage for local fishing. Same with the others, the breakwater on the coast of Manokwari also contact with the substrate directly, which is a habitat for Polychaeta. The lack of research data and information on Polychaeta in the Papua Sea encourages this research must be done. The purpose of this research is to identify the spesies of Polychaeta and analyze the impact of breakwater to the community structure of Polychaeta. This research conducted on March to June 2018 focus on six station of five beach with breakwater at the coastal of Manokwari, West Papua i.e. Abasi, Pasir Putih, Wosi, Andai and Mansinam Island. The line transect quadran method were use to collect sample of the Polychaeta. Total 64 sample of Polychaeta was collecting and identified.  Approximately 17 spesies of Polychaeta (i.e. seven orders, nine of families and 14 genera) already identified. Based on ANOVA and BNt tests, the breakwater development has significantly impacte to the structure community of Polychaeta on the coastal of Manokwari. ABSTRAKBreakwater atau pemecah gelombang merupakan struktur kecil yang didesain untuk melindungi area pesisir pantai dari paparan gelombang air laut yang ekstrim. Sama dengan lainnya, breakwater di pesisir pantai Manokwari juga bersentuhan langsung dengan substrat, yang merupakan habitat cacing laut, Polychaeta. Minimnya data penelitian dan informasi tentang Polychaeta di laut Papua mendorong penelitian ini dilakukan dengan tujuan mengidentifikasi spesies Polychaeta dan menganalisa dampak yang ditimbulkan dari breakwater terhadap struktur komunitas cacing taksa cacing laut ini. Penelitian ini dilaksanakan pada bulan Maret hingga Juni 2018 yang dipusatkan pada enam stasiun di lima pantai yang terdapat breakwater, yaitu pantai Abasi, Pasir Putih, Wosi, Andai dan pantai Pulau Mansinam. Garis transek kuadran sebagai metode pengambilan sampel Polychaeta. Sebanyak 64 sampel telah dikoleksi dan berhasil dikenali 17 spesies Polychaeta yang terbagi dalam tujuh ordo, sembilan familli dan 14 genus. Berdasarkan uji ANOVA dan Uji BNt menunjukan keselarasan pembangunan breakwater berdampak signifikan terhadap struktur komunitas Polychaeta di pesisir pantai Manokwari.